Perception and attitude of medical doctors in Dhaka, Bangladesh, with regard to Ayurvedic medicine - Yoshida, Yoshitoku (Nagoya J Med Sci, 2017)
The World Health Organization (WHO) Traditional Medicine Strategy (2014–2023) aimed to help member states promote the safe and effective use of traditional medicine. While economic conditions have markedly improved in Bangladesh, the country is experiencing significant public health problems. Because of limited medical resources, there is a strong incentive to enhance complementary and alternative medicine usage in Bangladesh. Therefore, this study aimed to confirm the perceptions and attitudes of medical doctors (MDs) in Dhaka, Bangladesh, with regard to Ayurvedic medicine (AM). A total number of 159 MDs in Dhaka were interviewed by face-to-face between February and June 2015. The study revealed that 62.0% of MDs had treated patients with AM and 55.3% believed that AM should be regarded as its own specialty, whereas 39.7% of MDs believed that AM should be part of the conventional medical curriculum and 32.7% thought that AM did not seem scientific. In terms of gender, 45.3% of male MDs agreed or strongly agreed that AM only had a placebo effect. On the other hand, 65.8% of female MDs disagreed or strongly disagreed it. In terms of age, 77.0% of MDs aged 36 or elder (elder MDs) believed they were more likely to recommend AM use and 80.3% of elder MDs believed that the government should encourage more initiatives to promote AM. To enhance AM use, scientifically robust information on the efficacy, safety and scientific basis of AM should be more effectively conveyed to male MDs.